Psychological interventions with paralympic athletes - Guerrero, M. D.; Martin, J. J.; Prokesova, E. (Advances in mental skills training, 2021)
Sport psychologists working with all athletes discover the idiosyncratic strengths and weaknesses they possess. Athletes vary tremendously based on their personality, sport, family experiences, and a host of other untold influences and decisions that shape who they are. Hence, despite the above observations about common experiences faced by athletes with disabilities (i.e., classification, motivation, injury, and pain), sport psychologists are advised to treat each athlete they work with as a unique individual. Moreover, there are many things to consider when designing, implementing, and delivering PST programs to athletes with disabilities. Underpinning all these considerations, the sport psychologist must remember one core principle: athletes with disabilities are athletes, and therefore the basic tenets of a PST still apply to this population. While mindfulness and gratitude originated from the positive psychology literature, the applicability of these approaches in disability sport appears promising. Consider, for example, a former able-bodied athlete who has acquired a permanent physical disability. Initially this athlete may have a difficult time coping with several life-altering changes, pain,